2021
DOI: 10.3390/ijerph18041771
|View full text |Cite
|
Sign up to set email alerts
|

Coping, Resilience, and Perceived Stress in Individuals with Internet Gaming Disorder in Taiwan

Abstract: Aim: Gaming escapism is an essential factor for developing internet gaming disorder (IGD). We evaluated coping strategies, resilience, stress, and depression in individuals with IGD. Methods: We included 69 participants with IGD and 138 controls (69 regular gamers and other non-gamers) in Taiwan. The self-reported coping strategies, coping stress with gaming, resilience, perceived stress, and depression were assessed. Results: Participants with IGD had higher dysfunctional coping, coping stress by gaming, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…Certain people are predisposed to acquiring GD due to their inability to control their gaming behaviors as a form of enjoyment. Individuals with GD account for 0.21-57.5% of the overall population [ 6 ]. For the first time, GD was included in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certain people are predisposed to acquiring GD due to their inability to control their gaming behaviors as a form of enjoyment. Individuals with GD account for 0.21-57.5% of the overall population [ 6 ]. For the first time, GD was included in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study observed that exposure to noise pollution, light pollution, and air pollution; poor-quality housing; a poor-quality diet; physical inactivity; and economic strain contributed to depression in urban areas [21]. Both depression and stress are associated with the risk of developing Internet addiction or gaming disorder [22,23]. Thus, psychological distress and depression potentially mediate the association between urbanization and Internet addiction [15 ▪▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Psychological resilience comprises three major protective mechanisms pertaining to individual capacities (e.g., personal skills, social skills), interpersonal relations (e.g., peer support, physical and psychological caregiving), and the availability of community resources and opportunities (e.g., spirituality, culture, education), respectively (25,26). These protective mechanisms strengthen a person's ability to handle an array of environmental and personal problems, such as daily stressors and interpersonal conflict (27).…”
Section: Introduction Backgroundmentioning
confidence: 99%